Pengaruh Group Investigation terhadap Hasil Belajar Fisika Peserta Didik pada Pokok Bahasan Gerak Lurus Kelas X di SMAN 1 Jabung Lampung Timur - Oktaviani, Eva; Diani, Rahma; Romlah, Romlah (Universitas Islam Negeri Raden Intan Lampung, 2018)
Abstract: As for the goal in this study are: To investigate the influence of the model learning Group Investigation (GI) to the learning outcomes of students in the Physics subject rectilinear motion class X SMAN 1 Jabung East Lampung. The method used is the method Quasi Experiment. Research conducted at SMAN 1 Jabung East Lampung and obtained class as a class experiment X4 and X2 class as the control class. Analysis of the data used t-test at the 0.05 level of significance of this can be seen thitung more than ttabel. From the research results, obtained by the average value of the final test on the control class is 69.67 with the qualification of